The clinical utility of cfRNA for disease detection and surveillance: A proof of concept study in non‐small cell lung cancer. Issue 15 (16th June 2022) - Metzenmacher, Martin; Hegedüs, Balazs; Forster, Jan; Schramm, Alexander; Horn, Peter A.; Klein, Christoph A.; Bielefeld, Nicola; Ploenes, Till; Aigner, Clemens; Siveke, Jens T.; Schuler, Martin; Lueong, Smiths S.
Abstract: Background: CT scans are used in routine clinical practice for the diagnosis and treatment surveillance of non‐small cell lung cancer (NSCLC). However, more sensitive methods are desirable. Liquid biopsy analyses of RNA and DNA can offer more sensitive diagnostic approaches. Cell‐free RNA (cfRNA) has been described in several malignancies, but its clinical utility has not previously been explored. Methods: We evaluated the clinical utility of cfRNA for early detection and surveillance of tumor disease in a proof‐of‐concept study. Using real‐time‐droplet digital polymerase chain reaction we characterized a candidate transcript ( MORF4L2 ) in plasma samples from 41 advanced stage, 38 early stage NSCLC and 39 healthy samples. We compared its diagnostic performance with tumor markers and evaluated its utility for disease monitoring. Results: MORF4L2 cfRNA was more abundant in patients than in healthy donors ( p < 0.0001 ). Using the Youden index approach (cutoff value of 537 copies/ml was established) with a sensitivity of 0.73 (95% CI: 0.61–0.82) and a specificity of 0.87 (95% CI: 0.73–0.96). Positive and negative predictive values of 0.92 (95% CI: 0.83–0.95) and 0.59 (95% CI: 0.47–0.83) were achieved. Combination of cfRNA and Cyfra21‐1 improved its predictive value from 89.5% to 94.7%. Low baseline MORF4L2 levels were associated with better overall survival (HR:0.25, 95% CI: 0.09–0.7, p = 0.009) and progression‐free survival for patients treated with tyrosine kinase inhibitors ( p = 0.011 ) and chemotherapy ( p = 0.019 ). MORF4L2 profile between baseline and follow‐up mirrored radiological response and tumor dynamics better than tumor markers. cfRNA transcripts allowed monitoring tumor dynamics in patients without tumor‐reported genetic alterations. Conclusion: Our data support clinical utility of cfRNA for detection and surveillance of NSCLC. Further studies with larger cohorts are required. Abstract : A substantial amount of cell‐free RNA(cfRNA) encountered in blood is free, circulating and not carried in extracellular vesicles. Combining cfRNA with the tumor marker CYFRA21‐1 improves its diagnostic strength and could allow for early detection of NSCLC and monitoring of treatment response. High plasma levels of the cfRNA transcript MORF4L2 were associated with poor overall survival.